ÁNGEL LÓPEZ-SIDRO LÓPEZ, Sonidos sagrados. Ruido y manifestaciones sonoras de la libertad religiosa, Dykinson, Madrid, 2021, 219 pp., ISBN: 9788413775289 - Alejandro González-Varas Ibáñez (Revista Española de Derecho Canónico, 2023)
Recensión